Essentials of corporate finance - Ross, Stephen A. (Irwin/McGraw-Hill, 1999)
"Essentials of Corporate Finance, 5/E" by Ross, Westerfield, and Jordan is written to convey the most important concepts and principles of corporate finance at a level that is approachable for a wide audience. The authors retain their modern approach to finance, but have distilled the subject down to the essential topics in 18 chapters. They believe that understanding the "why" is just as important, if not more so, than understanding the "how," especially in an introductory course.Three basic themes emerge as their central focus: an emphasis on intuition - separate and explain the principles at work on a common sense, intuitive level before launching into specifics. Underlying ideas are discussed first in general terms, then followed by specific examples that illustrate in more concrete terms how a financial manager might proceed in a given situation; a unified valuation approach - Net Present Value is treated as the basic concept underlying corporate finance. Every subject the authors cover is firmly rooted in valuation, and care is taken to explain how decisions have valuation effects; a managerial focus - Students learn that financial management concerns management.